PENINGKATAN EKSPOR KELAPA INDONESIA KE THAILAND TAHUN 2011-2015 - Mustamin, Rico; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia is a country with the largest coconut production in the world. This can be seen from Indonesia's exports which almost every year have increased with the aim of exporting to various countries. In 2011-2015 there was a decrease in the amount of coconut production, but from the export side, there was an increase at the same time. Likewise, exports of Indonesian coconut and coconut products to Thailand experienced an increase in 2011-2015. Of the many destination countries for Indonesian coconut exports, Thailand became the destination country with the largest increase in exports from Indonesia, while in the same period Indonesian coconut production experienced a decline. Therefore, this study aims to look at the factors causing the increase in Indonesian coconut exports to Thailand in 2011-2015.According to the liberal theory, market sovereignty in the economic process is very important, this theory assumes a natural harmony of interests between various people and various nations. Therefore, if individuals are left free to pursue their own interests in a trade economy based on a division of labor and on the structure or composition of the factors of their own production, the welfare of a group of individuals, a nation or a group of nations as a whole can be increased.The results of this study are, the increase in Indonesian coconut exports to Thailand that occurs due to the large demand for coconut from Thailand, so that from this large coconut demand, Indonesia allocates more coconut production towards exports, in this case Indonesia sees market opportunities that can used to get benefits from economic cooperation through export activities carried out. Keywords: export, coconut, increase, commodity, cooperation, agricultural sector